PENGUASAAN HARTA WARISAN SECARA MELAWAN HUKUM MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Heru Guntoro (Nusantara Hasana Journal, 2022)
The research case in the Decision of the Supreme Court of the Republic of Indonesia Number 889 K/Pdt/2018 in which the Business and Management of the Women's Clothing Trade Business "Dame Dame Trade" was inherited from the Plaintiff's late parents with a kiosk. Vak. I No. 100, in the Building. III. Floor. 2 Pematangsiantar Horas Market Center and subsequently handed it over to the heirs of the late Hesekiel Tampubolon and the late Elseida Br Marpaung who in this case were represented by the Plaintiff. To the Defendant to release and leave and surrender the Concession and Concession of a plot of land covering an area of ​​approximately 10 (ten) rante located in Matio Hamlet, Naga Huta Timur Village, Siantar District. The research method carried out by the author is normative legal research. This research is descriptive in nature, namely research that seeks to explain the solution to existing problems based on legal material, so it presents the legal material and then analyzes and interprets it. The results of this research conclude that a) Judge's consideration of unlawful acts over control of inheritance against rights in the MARI Decision Number 889 K/Pdt/2018, namely Article 1365 of the Civil Code where if the act fulfills the elements, namely there must be an act, the act must be against the law, there is an error on the part of the perpetrator (schuld), there is a loss for the victim and a causal relationship between unlawful acts and losses. These elements must be met cumulatively. b) Legal Consequences for Unlawful Acts of Control of Inheritance Against Rights in MARI Decision Number 889 K/Pdt/2018, namely the losses suffered by each Plaintiff and his siblings for the profits from the business and management of the women's clothing business. The trade of Dame inherited from the Plaintiff's parents by the Defendant is estimated at Rp.70,830,000.00 (seventy million eight hundred and thirty thousand rupiah).